Production of Food Flavouring Agents by Enzymatic Reaction and Microbial Fermentation - Panakkal, Elizabeth Jayex; Kitiborwornkul, Nichaphat; Sriariyanun, Malinee; Ratanapoompinyo, Jakaphan; Yasurin, Patchanee; Asavasanti, Suvaluk; Rodiahwati, Wawat; Tantayotai, Prapakorn (Applied Science and Engineering Progress, 2021)
Rising trends in the consumptions of food flavour compounds lead to motivation in the production of food flavours. The conventional techniques of flavour production are insufficient to produce flavour compounds according to the ascending demands of the market in terms of quantities and varieties. The current flavour production methods utilize chemical synthesis, which can produce a greater numbers of flavours with less time. However, the demand for natural products in consumables have created a necessity for new methodologies to produce flavour compounds with the label of “natural” origin. Emerging techniques in biotechnologies have enabled industries to produce compounds that can be considered natural. This review provides insights into the classification of flavour compounds and their production using microorganisms and enzymes in an ecofriendlier manner. The compounds produced by these techniques can be labelled as “natural” and can increase the market size of food flavours.